Arabic Teachers Pedagogical Competence: Cultural Approach in Enhancing the Students' Communicative Skills - Sanusi, Anwar; Hamid, M. Abdul; Nurbayan, Yayan; Ismail, Zawawi bin; Maulia, Lia Nurasriah (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
This research aims to discuss the pedagogical competence of Arabic teachers at the senior high school level (Madrasah Aliyah), focusing on cultural approaches to improve students' Arabic communicative skills. The research method used is a qualitative approach with a phenomenological type. This research involved classroom observations, in-depth interviews with the two teachers, and analysis of documents related to learning materials. The research results highlight two important things: First, the importance of selecting learning materials that suit students' needs and their level of understanding and paying attention to diverse learning interests and learning styles. Teacher 1 (T1) combines a book published by the Ministry of Religion of the Republic of Indonesia, Kurikulum Menteri Agama (KMA) 183 textbooks, with the silsilah ta'lim al-Lughah al-Arabiyyah pedigree to overcome the leading textbook's lack of Arabic cultural content. In contrast, teacher 2 (T2) integrates theoretical principles of language teaching with online learning resources and audiovisual materials. Second, this research shows that creating interactive, collaborative and communicative learning situations is essential in improving students' communicative competence. T1 uses question-and-answer techniques, discussions and group work, while T2 combines modern technology with learning videos, interactive applications and guided discussions. This research implies the importance of a cultural approach in improving students' Arabic communicative skills in Madrasah Aliyah. These findings can be the basis for developing a more inclusive and relevant curriculum in Arabic language learning at the high school level by paying attention to cultural aspects as an integral part of Arabic language teaching.